ANTIMICROBIAL SUBSTANCES: AN ALTERNATIVE APPROACH TO THE EXTENSION OF SHELF LIFE - Ekaterina A. Lukinova; Elena A. Kotenkova; Alexander N. Makarenko (Теория и практика переработки мяса, 2017)
The problem of high losses of raw materials and products in the food industry is reviewed in the article. Brief lists of spoilage types as well as the available approaches to meat preservation are discussed including technological, physical and chemical. Natural antimicrobial substances are considered as alternative approaches, the existence of which has been known for more than 60 years. Antimicrobial peptides are the evolutionary ancient factor of innate immunity and are found in the cells and tissues of vertebrate and invertebrate animals, plants, fungi and bacteria. Present approaches to their classification, structure and mechanisms of action are discussed. The information from the Antimicrobial Peptide Database and the UniProt Protein Database is systematized in relation to the presence of antimicrobial substances in the tissues of pigs and cattle. Such parameters as the molecular weight, isoelectric point, charge, amino acid sequence and share a hydrophobic part, as well as a range of activities: antibacterial, antifungal, antiviral, antiparasitic, etc. are presented in the article. On the basis of the review, alternative sources of antimicrobial proteins and peptides are proposed as well as technology for shelf life prolonging.